Laparoscopic ureterocalicostomy for ureteropelvic junction obstruction in a 10-year-old female patient: a case report - Nishimura, Yoko (BMC Res Notes, 2017)
BACKGROUND: Ureterocalicostomy is indicated mainly in cases with failed pyeloplasty or with a completely intrarenal pelvis. While there have been several case series reported in adults, laparoscopic ureterocalicostomy in pediatric cases has rarely been reported. We report a case of pure laparoscopic ureterocalicostomy for ureteropelvic junction obstruction in an Asian female child. CASE PRESENTATION: A 10-year-old female patient was referred to our hospital due to right high-grade hydronephrosis and a right renal stone, which was detected due to hematuria. Laparoscopic pyelolithotomy and ureterocalicostomy were indicated because of the completely intrarenal pelvis with thinning of the cortex, especially at the lower calyx. A transperitoneal approach was implemented in a lateral flank position with four trocars. After exposing the renal hilum, the renal stone was extracted without lithotripsy by making a small longitudinal incision at the ureteropelvic junction. Then, the ureter was transected, and the renal pelvis was closed. A 2-cm incision was made at the lower calyx. Uretero-caliceal anastomosis was completed in a running fashion using 5-0 absorbable sutures. The operation time was 379 min. The postoperative course was uneventful. Postoperative imaging studies showed marked improvement of the right hydronephrosis. CONCLUSION: Laparoscopic ureterocalicostomy is a safe and feasible treatment for selected patients with complicated ureteropelvic junction obstruction, even in the pediatric population.